THE CHOICE OF A RATIONAL CONNECTION OF THE TRANSFORMERS WINDINGS, STATIC CONVERTERS IN MODERN TEST BENCHES OF TRACTION ENGINE - Loza, P. O. (Science and Transport Progress, 2008)
In this article the expediency of delta connection of transformer windings in the static devices of test desk for locomotive traction engine is demonstrated.